Determinants of Students’ Intention to Become Tax Consultants - Selfira Salsabilla (Jurnal Proaksi, 2025)
Main Purpose - This study aims to analyze the influence of labor market considerations, subjective norms, self-efficacy-technical skills, and outcome expectations on the intention to become a tax consultant. Method - This study uses a quantitative method with the Structural Equation Modeling (SEM) approach. The research sample consisted of 170 students of the UII Tax Accounting study program. Main Findings - The results of the study indicate that students’ intention to become tax consultants is more influenced by subjective norms and outcome expectations. However, no influence of labor market considerations and self-efficacy of technical skills on the intention to become a tax consultant was found. Theory and Practical Implications - The results of the study show that the surrounding environment is a factor that influences becoming a tax consultant. Therefore, academics need to provide adequate information about the role of the current tax consultant profession. In addition, the results of this study can be a basis for companies that want to recruit tax consultants to provide compensation and rewards that are in accordance with their work. Novelty - This study elaborates on the Theory of Planned Behavior (TPB) and Social Cognitive Career Theory (SCCT) to explore students’ intentions to become tax consultants.